A New Thorny Lacewing (Insecta: Neuroptera: Rhachiberothidae) from the Early Cretaceous Amber of Lebanon - Petrulevicius, Julian Fernando (2010)
A new genus and species of Rhachiberothidae, Raptorapax terribilissima gen. et sp. nov. from the Cretaceous amber of Lebanon is described. The new genus is assigned to the subfamily Paraberothinae. The new material confirms the great diversity of the group in Cretaceous age and its decrease in diversity in recent times.